Knowledge, source and practice of spacing methods of contraception among eligible women of Varanasi slums - Singh, Payal; Mishra`, Akash; Mishra, Ravindra Nath (Indian Journal of Community Health, 2019)
Background: Still many Indian states observe low spaced births and high fertility above replacement level; mostly contributed by disadvantaged society. Factors influencing are entrenched in ignorance, male child desire and traditional culture to some extent. Aim and Objectives: To determine knowledge and practice of spacing methods of contraception and the associated socio-demographic variables. Settings and Design: Cross-sectional study Methods and Material: A community based cross-sectional study; conducted among 590 eligible couples of slum community of Varanasi selected following two stage stratified random sampling. First stage stratification was based on slum size and second stage was caste class group size. . Statistical analysis used: Knowledge and practice were described in percent and the associated factors were identified by logistic regression. Statistical significance was judged at ? = 0.05. Results: Overall knowledge of any spacing methods was in only 61.2% women and practice ever in married life was 44.4%, even those who knew the methods ever practice was only 66.2%. Knowledge gained was mostly through husband for condom, health professional for Cu-T and oral pills. In recent years (last 7 years), overall practice of spacing methods was only 30%. Contraception practice was association survival of child (lesser, if child surviving), number of births (higher, if more living born), religion (lesser, if Muslim), type of house (lesser, if living in hut/kachcha houses) and wife educational attainment (lesser, if low education level) Conclusion: Eligible couples of slum community need knowledge of contraception as well as motivation to practice spacing methods to reduce higher level of fertility. Keywords: Contraception, spacing methods, fertility